Purification and Characterization of Lipase enzyme from germinating soy bean seed - م.م. بتول محمود الانصاري . ا.د. علي احمد ساهي . ا.م.د. ضياء فالح الفكيكي ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
The study included purification and characterization of lipase enzyme from germinating soy bean seed, by following the gradually precipitated by addition of ammonium sulphate to final saturation of 20 -90%. Agradual obvious higher specific activity of the enzyme in the precipitate resulted ,till saturation level 80% , this step gave aspecific activity of 324.40 unit/ mg protein and an enzyme yield of 29.20% ,purification folds 10.79 time . Results for determination of lipase purity showed an appearance of a single protein band by poly acrylamide gel electrophoresis with out of denaturizing agent . The molecular weight of enzyme was 41.686 kilo dalton by poly acrylamide gel electrophoresis with denaturizing agent